Discrepancies and Disagreements in Classical Chamber Musicians' Characterisations of a Performance. (11th May 2021) - Spiro, Neta; Schober, Michael F.
To what extent do classical chamber musicians converge in their characterisations of what just happened in their live duo performance, and to what extent do audience members agree with the performers' characterisations? In this study a cello-piano duo performed Schumann's Phantasiestücke, Op. 73, no. 1 as part of their conservatory studio class in which members critique performances in development. Immediately after, the listeners and players individually characterised what had most struck them about the performance, first writing comments from memory and then marking scores while listening to a recording on their personal devices. They all then rated (on a 5-point scale) their agreement with comments by two other class members. Findings demonstrate that classical chamber performers can characterise the performance quite differently than their partner does and that they can disagree with a number of their partner's characterisations, corroborating previous findings in case studies of jazz performance. Performers' characterisations can overlap less in which moments strike them as worthy of comment and in their content than their listeners' characterisations do, and they can agree with a non-partner's characterisations more than with their partner's characterisations. At the same time, the data show that listeners who have played the piece before—though not necessarily those who play the same kind of instrument (strings vs. piano)—can be more likely to endorse comments by others who have also played the piece before, even if the comments they make don't overlap with each other more in timing, content or theme.